Students' awareness of Eco-Campus environmental activities and initiatives in the university: an evaluation - Norazah Mohd Suki; Norbayah Mohd Suki; Irma Wani Othman; Iftekhar Amin Chowdhury (Universiti Malaysia Sabah, 2014)
Drawing on literature utilizing the theory of planned behaviour, the present study examined the structural connection between attitudes toward environmental activities, subjective norms, and perceived behavioural control, and students' intention to engage with environmental activities and green initiatives in campus. Next, this study also investigated the relationship between a) personal willingness towards environmental activities, b) attitudes towards personal responsibility, and c) attitudes toward the faculty's responsibility for creating a sustainable environment, and intention to engage in eco-campus environmental activities and green initiatives. Structural equation modelling (SEM) was used to test a model. The research also used multiple regressions for data analysis in an attempt to achieve the objective across a sample of 374 students in a public university in Sabah, Malaysia. The research results of SEM showed that the link between perceived behavioural control positively affects students' intention to engage with environmental activities and green initiatives in campus are significantly proven at p<0.05. This implies that positive behavioural control is held when students regarded 'If I wanted to I could easily engage in environmental activities' as the most popular issue. For control beliefs, students also pointed out that item 'For me to engage in environmental activities is easy' was also another important consideration regarding intention to engage with environmental activities and green initiatives in campus. Next, empirical results of multiple regressions revealed that personal willingness towards environmental activities, and attitudes towards the faculty's responsibility for creating a sustainable environment significantly affect students' intention to engage with eco-campus environmental activities and green initiatives. The first was found to have the strongest effect. The research provides a unique perspective of students' intention to engage with eco-campus environmental activities and green initiatives, which has previously not been much covered in the Malaysia context. The measurement produced can be used as a research tool for more exploratory and explanatory research regarding the investigated issues. Direction for future research is also presented.